Sociodemographic Patterns of Urine Sodium Excretion and Its Association with Hypertension in Chile: A Cross-Sectional Analysis - Iturra-Gonzalez, J; Garcia-Hermoso, A (Cambridge University Press, 2019)
Objective The aim of the study was to determine the main factors (sociodemographic, anthropometric, lifestyle and health status) associated with high Na excretion in a representative population of Chile.Design Na excretion (g/d), a valid marker of Na intake, was determined by urine analysis and Tanaka s formulas. Blood pressure was measured by trained staff and derived from the mean of three readings recorded after 15 min rest. The associations of Na excretion with blood pressure and the primary correlates of high Na excretion were determined using logistic regression.Setting Chileans aged ≥15 years.Participants Participants (n 2913) from the Chilean National Health Survey 2009-2010.Results Individuals aged 25 years or over, those who were obese and those who had hypertension, diabetes or metabolic syndrome were more likely to have higher Na excretion. The odds for hypertension increased by 10·2 % per 0·4 g/d increment in Na excretion (OR=1·10; 95 % CI 1·06, 1·14; P < 0·0001). These findings were independent of major confounding factors.Conclusions Age, sex, adiposity, sitting behaviours and existing co-morbidities such as diabetes were associated with higher Na excretion levels in the Chilean population. These findings could help policy makers to implement public health strategies tailored towards individuals who are more likely to consume high levels of dietary salt. © The Authors 2019.